2011
DOI: 10.1002/jor.22005
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet‐rich plasma stimulates migration and chondrogenic differentiation of human subchondral progenitor cells

Abstract: In cartilage repair, platelet-rich plasma (PRP) is used in one-step approaches utilizing microfracture and matrix-induced chondrogenesis procedures, bone marrow-derived cell transplantation, or intra-articular injection. The aim of our study was to evaluate the effect of human PRP on the migration and chondrogenic differentiation of human subchondral progenitors. Human progenitors were derived from subchondral cortico-spongious bone (CSP), were analyzed for their migration capacity upon PRP treatment in 96-wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
124
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 40 publications
(50 reference statements)
8
124
3
3
Order By: Relevance
“…SaOS-2 cell line, was shown by reverse transcriptionpolymerase chain reaction to express both PDGF-a and -b receptors. 15 Several other types of cells, beside osteoblasts, have been shown to acquire migration capacity and in some cases to undergo cytoskeletal changes when primed with PDGF: among them hepatic stellate cells, 23 marrow-derived mesenchymal stem cells, 24 malignant mesothelioma cells, 25 subchondral progenitors, 26 gingival fibroblasts. 27 The clinical use of PRP has recently experienced a surge in different indications and in particular in the procedures involving healing and tissue regeneration, as in dental and oral surgery, 9 in bone deficiency healing, 3,7,10 in the treatment for tendon and ligament injuries, 8,11 in the pathologic processes of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…SaOS-2 cell line, was shown by reverse transcriptionpolymerase chain reaction to express both PDGF-a and -b receptors. 15 Several other types of cells, beside osteoblasts, have been shown to acquire migration capacity and in some cases to undergo cytoskeletal changes when primed with PDGF: among them hepatic stellate cells, 23 marrow-derived mesenchymal stem cells, 24 malignant mesothelioma cells, 25 subchondral progenitors, 26 gingival fibroblasts. 27 The clinical use of PRP has recently experienced a surge in different indications and in particular in the procedures involving healing and tissue regeneration, as in dental and oral surgery, 9 in bone deficiency healing, 3,7,10 in the treatment for tendon and ligament injuries, 8,11 in the pathologic processes of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown better results with the addition of platelet-rich plasma (PRP) to the conventional microfracture or drilling techniques. [29,42] Specimens treated with PRP show improved staining for type II collagen and proteoglycans, when compared to untreated specimens [43].…”
Section: Biologic Enhancement Of Microfracture Techniquementioning
confidence: 99%
“…Some in vitro studies have shown that PRP and MSCs can act synergistically to promote tissue regeneration (Mishra et al, 2009;Van Pham et al, 2013). The "chemoattractant" property of PRP may lead to recruitment of other cell types that will migrate to damaged tissues, thereby stimulating repair responses (Krüger et al, 2012).…”
Section: Introductionmentioning
confidence: 99%